Against the Backdrop of Traditions: A Study of Manju Kapur’s Heroines - MUKUNDRAO MORE, Dr. DATTATRAYA (International Journal of Multidisciplinary Research and Studies, 2022)
The current research paper aims to examine Manju Kapur's novels, specifically Difficult Daughters (1998), which won her the Commonwealth Prize in the Eurasia Section, A Married Woman (2003), Home (2006), and Custody (2011), to examine the role of her heroines against the backdrop of the traditions and conventions of the male-dominated society, in Manju Kapur's novels. This research paper aims to look at how Manju Kapur portrays the difference between traditional and modern values and how her heroines make their independent ways through the adverse conditions laid by conventional Indian societies.